Multiplex PCR assay for the identification of eight Anopheles species belonging to the Hyrcanus, Barbirostris and Lindesayi groups - Bang, Woo Jun (Malar J, 2021)
BACKGROUND: Genus Anopheles mosquitoes are the primary vectors of human malaria, which is a serious threat to public health worldwide. To reduce the spread of malaria and identify the malaria infection rates in mosquitoes, accurate species identification is needed. Malaria re-emerged in 1993 in the Republic of Korea (ROK), with numbers peaking in 2004 before decreasing to current levels. Eight Anopheles species (Anopheles sinensis, Anopheles pullus, Anopheles belenrae, Anopheles lesteri, Anopheles kleini, Anopheles sineroides, Anopheles koreicus, Anopheles lindesayi) are distributed throughout Korea. Members of the Anopheles Hyrcanus group currently cannot be identified morphologically. The other species of Anopheles can be identified morphologically, except when specimens are damaged in traps. The purpose of this study was to develop a rapid and accurate method for simultaneous molecular identification of the eight Anopheles species present in the ROK. METHODS: Anopheles spp. used in this study were collected near/in the demilitarized zone in ROK, where most malaria cases are reported. DNA from 165 of the Anopheles specimens was used to develop a multiplex PCR assay. The internal transcribed spacer 2 (ITS2) region of each species was sequenced and analysed for molecular identification. RESULTS: DNA from a total of 165 Anopheles specimens was identified to species using a multiplex diagnostic system. These included: 20 An. sinensis, 21 An. koreicus, 17 An. lindesayi, 25 An. kleini, 11 An. lesteri, 22 An. sineroides, 23 An. belenrae, and 26 An. pullus. Each species was clearly distinguished by electrophoresis as follows: 1,112 bp for An. sinensis; 925 bp for An. koreicus; 650 bp for An. lindesayi; 527 bp for An. kleini; 436 bp for An. lesteri; 315 bp for An. sineroides; 260 bp for An. belenrae; and, 157 bp for An. pullus. CONCLUSION: A multiplex PCR assay was developed to identify Anopheles spp. distributed in ROK. This method can be used to accurately identify Anopheles species that are difficult to identify morphologically to determine species distributions and malaria infection rates.